Interconnection and prioritization - Pio Baake; Slobodan Sudaric (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
We analyze pricing and competition under paid prioritization within a model of interconnected internet service providers (ISPs), heterogeneous content providers (CPs) and heterogeneous consumers. We show that prioritization is welfare superior to a regime without prioritization (network neutrality) and yields higher incentives for investment in network capacities. As ISPs price discriminate between on-net and off-net CPs, their bottleneck property is propagated and competition for consumers increases resulting in a potential prisoner's dilemma when deciding whether to offer prioritization. We show that peering for prioritized traffic emerges as a collusive outcome and present off-net prices as a further collusive instrument.
Keywords: L13; L51; L96; 330; interconnection; investment; network neutrality; prioritization